Pulmonary delivery of liposomal dry powder inhaler formulation for effective treatment of idiopathic pulmonary fibrosis - S. Chennakesavulu; A. Mishra; A. Sudheer; C. Sowmya; C. Suryaprakash Reddy; E. Bhargav (Elsevier, 2018)
Dry powder inhaler Liposomes were prepared to investigate the effectiveness of pulmonary delivery of Colchicine and Budesonide for Idiopathic Pulmonary fibrosis. Budesonide (BUD) and Colchicine (COL) liposomes were prepared by thin layer film hydration method (TFH) using 1,2-Dipalmitoyl-sn-glycero-3- phosphoglycerol sodium (DPPG), Hydrogenated Soyaphosphotidylcholine (HSPC), Soyaphosphatidylcholine (SPC), cholesterol (CHOL) and drug in different weight ratios. The optimum lipid composition for BUD (74.22 ± 0.97%) was DPPG: HSPC: CHOL (4:5:1) and for COL (50.94 ± 2.04%) was DPPG: SPC: CHOL (3:6:1). These compositions retained drug for a longer period of time so selected for further study. Liposomes were found to be spherical in shape with mean size below 100 nm. Liposomes lyophilized using Mannitol as carrier and cryoprotectant showed high entrapment efficiency (97.89 - 98.6%). The powder was dispersed through an Andersen cascade impactor to evaluate the performance of the aerosolized powder. It was found that prepared liposomal dry powder inhaler (DPIs) sustained the drug release up to 24 hours. Optimized Budesonide DPI Formulation B2 (86.53 ± 1.9%), Colchicine DPI Formulation C2 (90.54 ± 2.3 %) and BUD and COL DPI Combination M2 (89.91 ± 1.8%, 91.23 ± 1.9%). Histopathological results, measurements of lung hydroxyproline content, Myeloperoxidase activity indicated that liposomal dry powder inhaler administration attenuates lung fibrosis induced by bleomycin. Long term stability studies indicated that lyophilised BUD and COL liposomes were stable for 6 months at (25 °C ± 2 °C, 60% ± 5% RH) and refrigerated conditions (2 - 8 °C). These results supported that combination of budesonide and colchicine liposomal dry powder inhaler pulmonary drug delivery for treatment of idiopathic Pulmonary Fibrosis exhibits prolonged drug retention at targeted site and reduces the systemic exposure.